Stream sediments as a repository of U, Th and As around abandoned uranium mines in central Portugal: implications for water quality management - Carvalho, Paula (2022)
This work focuses on the study of water–sediment interaction around abandoned uranium mines with open-pit lakes and mine dumps. Nineteen water and eleven stream sediment samples were collected in the abandoned Barrôco D. Frango mine, central Portugal. The trace element distribution was compared with other abandoned uranium mines in Portugal and worldwide. Generally, U, Th, and As contents in the open-pit water are high and similar to those of downstream water, suggesting its influence on aquatic systems. In abandoned mines with small to medium U exploitation, the stream sediments are moderately to heavily contaminated with U, Th and As, being U and As the most important contaminants, confirmed by their partition coefficients. A moderate to considerable potential ecological risk (34–79) was found around the abandoned Barrôco D. Frango mine area, mainly due to As contents in stream sediments. Water and stream sediments from abandoned U mines worldwide have U levels of up to 436 μg/L and 5024 mg/kg, respectively, while those from Barrôco D. Frango have 37.3 μg/L and 189 mg/kg, respectively. However, the longer the distance from the Barrôco D. Frango open-pit lake and mine dump, the higher U, Th and As contents in stream sediments, which is a warning indicator. Cluster heat maps of the water composition from four abandoned uranium mine areas show that Mondego Sul and Barrôco D. Frango mines are the most geochemically similar. Results show that stream sediments should be included in water quality management and future remediation plans of abandoned uranium mines.